Campanian ammonites from the Upper Cretaceous Gober Chalk of Lamar County, Texas - Cobban, W; Kennedy, W (1992)
The Roxton Limestone Member at the top of the Gober Chalk in northeast Texas yields a rich fauna, dominated by Baculites haresi Reeside, 1927, and Inoceramus balticus Boehm, 1909, with sparse occurrences of pachydiscus cf. P. paulsoni (Young, 1963), Anapachydiscus sp.juv., Placenticeras placenta (DeKay, 1828), Hoplitoplacenticeras aff. H. plasticum (Paulcke, 1907), Menabites (Delawarella) delawarensis (Morton, 1830), M.(D.) danei (Young, 1963), M.(D.) aff. M.(D.) vanuxemi (Morton, 1830), Submortoniceras vandalinaense Young, 1963, Submortoniceras sp., Eubostrychoceras sp., and Scaphites hippocrepis (DeKay, 1828) III. The presence of S. hippocrepis III suggests a late early Campanian age assignment for the fauna. The assemblage includes species known from the Western Interior, Gulf Coast, Atlantic seaboard, and western Europe. -Authors